Theoretical Approach to Study Assembly Nature of Molecular Modeling System of Carbon Nanotube and a Nematic Liquid Crystal - Rashad, Alaa Adnan; Jber, Nasreen Raheem; Shihab, Mehdi Salih (Al-Nahrain Journal of Science, 2018)
Theoretical study for stable geometries of a nematic liquid crystal (LC) molecule assembled on the carbon nanotubes (CNT) wall by using semi-empirical molecular quantum calculations within the PM3 method as implemented in Hyperchem package. The interaction influence of ,-stacking between N-4`-Methoxybenzylidine-4-n-butylaniline (MBBA) liquid crystal molecule on the CNT wall led to formation of the local short range orientation order by LC molecules on the surface of the CNT due to the LC-CNT binding energy (,-stacking). The binding energy of the LC molecule on the CNT wall was within the typical van der Waals interaction. This binding originated from the electrostatic energy by a significant amount of charge transfer from the LC molecule to the CNT.